2012
DOI: 10.5657/kfas.2012.0379
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of the Pacific Cod Gadus macrocephalus in the Coastal Waters off Jumunjin, Gangwondo of Korea

Abstract: The feeding habits of the Pacific cod Gadus macrocephalus were studied by analyzing the stomach contents of 423 specimens caught by coastal gill net in the coastal waters off Jumunjin, Gangwondo, Korea, from January to December, 2011. The size of Pacific cod ranged from 31.0 to 86.5cm in total length (TL). The proportion of empty stomachs was 25.1%. The main prey items were Macrura, Pisces, and Cephalopoda. In order of abundance, the most dominant species of Macrura, were Pandalus eous, Argis lar, and Neocrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These results suggest that G. microcephalus is an intermediate predator with both pelagic and benthic diets. Yoon et al (2012) found that smaller individuals of G. macrocephalus (30-55 cm in total length) feed mainly on macruran crustaceans, while fish were the main diet of larger individuals (over 56 cm) with a relatively high TL. By contrast, A. japonicus individuals were found only in November and had lower δ 13 C and δ 15 N values (− 20.1 ± 0.5 and 11.2 ± 0.5‰, respectively), which suggests that their main prey items might be zooplankton and pelagic prey with lower isotopic values.…”
Section: Characteristics In the Food Web Structure Of Fish Consumersmentioning
confidence: 96%
“…These results suggest that G. microcephalus is an intermediate predator with both pelagic and benthic diets. Yoon et al (2012) found that smaller individuals of G. macrocephalus (30-55 cm in total length) feed mainly on macruran crustaceans, while fish were the main diet of larger individuals (over 56 cm) with a relatively high TL. By contrast, A. japonicus individuals were found only in November and had lower δ 13 C and δ 15 N values (− 20.1 ± 0.5 and 11.2 ± 0.5‰, respectively), which suggests that their main prey items might be zooplankton and pelagic prey with lower isotopic values.…”
Section: Characteristics In the Food Web Structure Of Fish Consumersmentioning
confidence: 96%
“…(Cha and Jung, 2012). (Seo et al, 2007;Lee et al, 2005;Cha et al, 2007), (Kim et al, 2013), (Choi and Gwak, 2011) , Park and Gwak (2009), , Yoon et al (2012), Baeck et al (2007, Seo et al (2010), Gwak and Nakayama (2011) , .…”
Section: 서 론 (Gadus Microcephalus)mentioning
confidence: 99%
“…(Park, 2005;Park et al, 2007) . (Huh and Kwak, 1998a), (Baeck et al, 2007), , , (Huh et al, 2006;Yoon et al, 2008;Huh et al, 2011) , , , (Choi et al, 2009), (Lee et al, 2007), (Yoon et al, 2012) . , , .…”
Section: 서 론mentioning
confidence: 99%